Phosphorus starvation response and PhoB-independent utilization of organic phosphate sources by Salmonella enterica - Roberto E. Bruna; Christopher G. Kendra; Mauricio H. Pontes (Microbiology Spectrum, 2023)
ABSTRACT Inorganic orthophosphate (Pi, PO4 3−) is the preferred phosphorus (P) source of most living cells. In enteric bacterial species such as Salmonella enterica serovar Typhimurium (Salmonella), removal of Pi from the growth medium activates a dedicated two-component signal transduction system which is composed of the membrane-bound sensor kinase PhoR and its cognate transcriptional regulator PhoB. Activated PhoB promotes transcription of genes that are involved in adaptations to low Pi conditions, such as high-affinity Pi transporters and genes required for the assimilation of alternative P sources, allowing bacteria to adapt to low Pi environments. Here, we characterize the PhoB-dependent and independent transcriptional changes elicited by Salmonella in response to P starvation. We identify a set of organic molecules that can serve as the sole P source and pinpoint genes that are involved in their assimilation. Intriguingly, a number of these genes are not under PhoB/PhoR control, indicating that in the absence of environmental Pi, Salmonella may fulfill its biosynthetic demands for P without activating a transcriptional response to Pi starvation. IMPORTANCE Phosphorus (P) is the fifth most abundant element in living cells. This element is acquired mainly as inorganic phosphate (Pi, PO4 3−). In enteric bacteria, P starvation activates a two-component signal transduction system which is composed of the membrane sensor protein PhoR and its cognate transcription regulator PhoB. PhoB, in turn, promotes the transcription of genes that help maintain Pi homeostasis. Here, we characterize the P starvation response of the bacterium Salmonella enterica. We determine the PhoB-dependent and independent transcriptional changes promoted by P starvation and identify proteins enabling the utilization of a range of organic substrates as sole P sources. We show that transcription and activity of a subset of these proteins are independent of PhoB and Pi availability. These results establish that Salmonella enterica can maintain Pi homeostasis and repress PhoB/PhoR activation even when cells are grown in medium lacking Pi.